Analisis Keputusan Mahasiswa Memilih Program StudiDitinjau Dari Peringkat Akreditasi Dan PeluangKerja Guru Akuntansi Mahasiswa Fkip AkuntansiUniversitas Muhammadiyah SurakartaTahun 2015 - Pratami, Kuswindi Astuti Nur; , Dr. Sabar Narimo,MM.,M.Pd (2016)
Kuswindi Astuti Nur Pratami/ A210120067. STUDENT DECISION ANALYSIS ON CHOOSING PROGRAM RATING BASED ON ACCREDITATION AND ACCOUNTING TEACHER EMPLOYMENT OPPORTUNITIES OF ACCOUNTING STUDENT IN FKIP OF MUHAMMADIYAH UNIVERSITY OF SURAKARTA YEAR 2015. Thesis. The Faculty of Education, Muhammadiyah University of Surakarta, Juni, 2016. This research aims to find out; 1) Influence the ranking of accreditation of students choose a course of study; 2) influence of job opportunities accounting teacher of students choose a course of study; 3) Influence ranking and accreditation job opportunities accounting teacher of students choose a course of study. This research included quantitative descriptive research type with the withdrawal of the conclusion through statistical methods. The population in the study are all students FKIP Accounting forces 2015 as many as 240. Samples taken as many as 148 students with sample random sampling. Required data obtained from the question form and documentation. Previously now the tested and tested reliability validity. Data analysis technique used multiple linear regression analysis, t-test, F-test, a test of determination coefficient, relative donations and donations effectively. The results of the regression analysis regression line equation is obtained; Y = 7.554 + 0, 269X1 + 0, 350X2. The equation shows that the decision of the student choosing a study program accreditation and rankings are affected by job opportunities accounting teacher. The conclusions drawn are: 1) The accreditation Rankings of college students choose a course of study acceptable. It is based on multiple regression analysis (test t) Note that thitung > t tabel, 5.300 > 1.976 and value signnifikasi < 0.05, i.e. the relative contributions of 0.000 53% and the effective contribution of 23,53% ; 2) Job opportunities accounting teacher of students choose a course of study acceptable. This is based on an analysis of the multiple linear (t-test) note that t count > t table, namely 4.868 > value and significance of 1.976 < 0.05, i.e. the relative contributions of 0.000 47% and the effective contribution of 21,12%. 3) Accreditation and Ranking job opportunities accounting teacher of students choose a course of study acceptable. This is based on multiple linear regression analysis of variations (fr F) note that Fcount > Ftable, namely 58.601 > 3.058 significance and value, i.e. 0.05 < 0.000. 4) The coefficient of determination (R2) of 0.447 showed that the magnitude of the influence ranking and accreditation job opportunities accounting teacher against the decision of choosing a course is of 44.7%, while the rest in influence other variables.